2020
DOI: 10.1038/s41398-020-0700-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurometabolic correlates of 6 and 16 weeks of treatment with risperidone in medication-naive first-episode psychosis patients

Abstract: Antipsychotic medications are the cornerstone of treatment in schizophrenia spectrum disorders. In first-episode psychosis, the recommended time for an antipsychotic medication trial is up to 16 weeks, but the biological correlates of shorter and longer antipsychotic treatment trials in these cohorts remain largely unknown. We enrolled 29 medication-naive first-episode patients (FEP) and 22 matched healthy controls (HC) in this magnetic resonance spectroscopy (MRS) study, examining the levels of combined gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Although we had sufficient power to detect if paired differences were present in the patient group, any interaction is likely underpowered. We observed a small glutamate decrease in healthy control (0.06 mM/y), comparable to the effect size observed in Birur et al 54 with 16 patients and 14 HC. Bayesian statistical approaches are based on an expected prior distribution and not influenced by the central limit of sample size placed on conventional statistics.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although we had sufficient power to detect if paired differences were present in the patient group, any interaction is likely underpowered. We observed a small glutamate decrease in healthy control (0.06 mM/y), comparable to the effect size observed in Birur et al 54 with 16 patients and 14 HC. Bayesian statistical approaches are based on an expected prior distribution and not influenced by the central limit of sample size placed on conventional statistics.…”
Section: Discussionsupporting
confidence: 90%
“…Prior longitudinal studies at lower field strengths have been equivocal on the issue of progressive glutamatergic reduction in schizophrenia. 7 Synthesizing this longitudinal literature, Egerton et al 53 noted an almost even split between studies that reported significant glutamate decrease in at least one brain region and studies reported no glutamate reduction, with at least 3 further studies showing no longitudinal glutamate reduction in the ACC after 6 weeks, 27 , 54 , 55 4 months, 54 and 9 months. 27 Our findings are more aligned with these recent studies as well as the lack of progressive ACC glutamate change reported by Bustillo et al 26 (at 1, 6, 12 months) and Théberge et al 10 (10 months) at 4T.…”
Section: Discussionmentioning
confidence: 99%
“…Although we had sufficient power to detect if paired differences were present in the patient group, any interaction is likely underpowered. We observed a small glutamate decrease in healthy control (0.06 mM/year), comparable to the effect size observed in Birur et al 51 with 16 patients and 14 healthy controls. Bayesian statistical approaches are based on an expected prior distribution and not influenced by the central limit of sample size placed on conventional statistics.…”
Section: Discussionsupporting
confidence: 90%
“…Prior longitudinal studies at lower field strengths have been equivocal on the issue of progressive glutamatergic reduction in schizophrenia 7 . Synthesizing this longitudinal literature, Egerton et al 50 noted an almost even split between studies that reported significant glutamate decrease in at least one brain region and studies reported no glutamate reduction, with at least 3 further studies showing no longitudinal glutamate reduction in the ACC after 6 weeks 27,51,52 , 4 months 51 , and 9 months 27 . Our findings are more aligned with these recent studies as well as the lack of progressive ACC glutamate change reported by Bustillo et al 26 [at 1, 6, 12 months] and Théberge et al 10 [10 months] at 4T.…”
Section: Discussionmentioning
confidence: 99%
“…In magnetic resonance spectroscopy studies, we found elevated choline and a disruption of the relationship between NAA and glutamate in the left striatum, indicating possible mitochondrial, membrane, and glial dysfunction ( 72 ). However, we reported no neurometabolite abnormalities in the medial prefrontal cortex or the hippocampus when contrasting antipsychotic medication-naïve first episode patients and controls in the overall group ( 31 , 69 ). It is important to note that glutamate levels in both areas showed a greater variance in patients compared to controls, suggesting heterogeneity in glutamatergic metabolism in first episode psychosis.…”
Section: Key Scientific Questions In Neuroimaging Research In Schizopmentioning
confidence: 58%